Severe Acute Pancreatitis: A Possible Role of Intramyocardial Cytokine Production - Meyer, Alberto; Kubrusly, Márcia S; Salemi, Vera M; de Mendonça Coelho, Ana M; Molan, Nilza A T; Patzina, Roseli A; Machado, Marcel C C; Mady, Charles; D’Albuquerque, Luiz A C; Jukemura, José (JOP. Journal of the Pancreas, 2014)
Context Several mechanisms are involved in the development of the local and systemic response in acute pancreatitis. Cardiovascular system may be affected throughout the clinical course of acute pancreatitis. The aim was to evaluate local myocardial cytokine production, as well as, functional and histological myocardial alterations in severe acute pancreatitis. Methods The animals were divided into three groups: Group 1: control; Group 2: sham; Group 3: severe acute pancreatitis. Echocardiographic assessment of cardiac function, serum levels of amylase and cytokines (TNF-α, IL-6 and IL-10), and mRNA expression of TNF-α, IL-6 and TGF-β were measured. Myocardial tissue alterations were analysed by histological examination. Results The serum TNF-α and IL-10 levels were significant higher in AP 2h group. The mRNA IL-6 levels from group AP 2h were statistically higher. The mRNA TNF-α level from sham group and AP 2h were statistically lower. Significant changes in the left ventricular diameter were found in AP 2h and AP 12h groups. There were statistical changes for vacuolar degeneration, picnosis and loss of nucleus, and lymphocytes. Conclusion We found cardiac and histological changes compatible with the inflammatory process triggered by SAP with the promotion of local myocardial cytokine production. Image: Boxplot of LVEDD.